Physical education in cross-disciplinary approach in elementary school - Ignjatović Aleksandar M.; Miloradović Bojan D. (University of Kragujevac - Faculty of Pedagogy, Užice, 2018)
In modern way of life in which technology digitizes and "relieves" most of the everyday activities of children and adults, but also fully occupies their attention, there is a need for an interdisciplinary approach to physical education in all school curricula. This is because we are witnessing an increase in chronic diseases, such as obesity in children caused by their reduced physical activity. Interdisciplinary teaching of physical education is offered as one of the solutions to this problem. It can increase the daily physical activity of pupils during their stay in school, but also in extracurricular activities. By integrating the content of the physical education curriculum into other teaching contents, the active time of training can be increased, and the academic achievements of the students can also be improved. This paper presents the position of physical education in schools, its importance in life and education of young people, as well as examples and possibilities of overcoming current problems of reduced physical activity in children.